2020
DOI: 10.1063/5.0008148
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the piezoelectric vibration of Pb(Mg1/3Nb2/3)O3-0.25PbTiO3 single crystal by alternating current polarization for ultrasonic transducer

Abstract: Alternate current poling (ACP) is an effective method to enhance the piezoelectric performance of Pb(Mg1/3Nb2/3)O3-xPbTiO3 (PMN-xPT) single crystals dramatically. For their application in piezoelectric transducers for medical imaging, the beam mode vibration of PMN-0.25PT single crystal resonators after ACP was investigated by combining experimental impedance measurements and finite element simulation. The complete material coefficients of PMN-0.25PT single crystals were obtained by using pulse-echo ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…With optimized ACP conditions of 5.8 kV cm −1 at 50 Hz for 20 cycles, the T 33 e /ε 0 and d 33 at RT of the preDCP + ACP SC improved to 7120 and 2610 pC/N, which were 48% and 54% higher than that of the DCP SCs. Zhang et al 52,53) of SICCAS reported finite element modeling simulation and comparison of electroacoustic properties for ACP phased arrays and DCP phased arrays. The (c) pinning effect of DCP caused some dipoles not to reverse after poling; (d) ACP with a sine signal made the dipoles reorient to the positive direction after several cycles; (e) ACP more easily eliminates the pinning effect during P s reversal with the negative direction; (f) saturated polarization switching finished after the ACP field moved out.…”
Section: Principles and Research History Of Acpmentioning
confidence: 99%
“…With optimized ACP conditions of 5.8 kV cm −1 at 50 Hz for 20 cycles, the T 33 e /ε 0 and d 33 at RT of the preDCP + ACP SC improved to 7120 and 2610 pC/N, which were 48% and 54% higher than that of the DCP SCs. Zhang et al 52,53) of SICCAS reported finite element modeling simulation and comparison of electroacoustic properties for ACP phased arrays and DCP phased arrays. The (c) pinning effect of DCP caused some dipoles not to reverse after poling; (d) ACP with a sine signal made the dipoles reorient to the positive direction after several cycles; (e) ACP more easily eliminates the pinning effect during P s reversal with the negative direction; (f) saturated polarization switching finished after the ACP field moved out.…”
Section: Principles and Research History Of Acpmentioning
confidence: 99%
“…3(g) and 3(h). 16,17) Figure 3(i)-3(l) indicated k′ 33 mode vibration with a range from 1 M to 25 MHz. Some SMVs between the fundamental mode and overtone mode were observed, which means non-uniform domain structures and ferroelectric phases were induced by the dicing.…”
Section: Resultsmentioning
confidence: 99%
“…15) Xu and Zhang et al reported the finite element modeling (FEM) simulation of DCP and ACP PMN-0.25PT SCs (L14.5 × W0.2 × T0.4 mm 3 ) for phased array ultrasonic transducers using rectangular beam-mode samples grown by the OC-BM method, with a center frequency of 3 MHz. 16,17) Wan and Luo et al revealed its effectiveness for sliver-mode DCP and ACP PMN-0.27PT SCs (L20 × W2 × T6 mm 3 ) grown by the OC-BM method with resonance frequency lower than 150 kHz. 18,19) Furthermore, Ma et al showed the performance of DCP and ACP 1-3 piezocomposite materials (10 × 10 × 1 mm 3 ) under various poling conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The change of shear piezoelectric properties can also be caused by the distorted lattice after ACP. [ 32 ] In addition, the ACP can make relaxor–PT ferroelectric single crystals with the new phase, such as monoclinic phase. Based on polarization rotation mechanism, [ 1 ] the new phase provides a flatter polar rotation path for polarization rotation.…”
Section: Resultsmentioning
confidence: 99%